A Review of Cholesterol's Dual Impact: Human Health and Environmental Consequences - Niran, Ayanniyi (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
Abstract Indiscriminate consumption of fatty foods especially those with higher percentage of saturated fatty acids in and around the world is likely to be in excesses in few years to come. This is particularly so owing to man detrimental eating habits. And this portends a potential risk for coronary heart diseases among unsuspecting consumers. Although man has the enzymatic capacity to convert excess fatty acids to harmless substrates within the body system, but there occur serious pressure on such functions when they are in excesses of the normal daily body requirement. The impact of heavily rich fat meals to the large supply of total fats and its saturated fatty acids derivatives in the human system has been largely traced to dietary intake of lipid rich diets. Their consequential effect over time can damage arteries, contribute to heart disease, and even stroke among unsuspecting consumers. Incidentally this has been traced to cholesterol (lipoprotein), a waxy substance that the body requires to perform certain critical functions including digestion, circulation, and growth and even the nervous system regulation. There are two distinct forms are known these lipoproteins; high density and Low density lipoproteins. Even though both are essential, the excessive intake of the low-density lipoprotein (LDL) is dangerous could trigger certain cardiovascular diseases and even death due to its excessive accumulation in the body. In spite of these foregoing however, they plays very critical roles in the life of virtually all living organisms including man. Therefore it harps on the study for a comprehensive review about the concept and dispels the misinformation about the significance and implication of effects of both saturated and unsaturated fatty acids as probable precursor for certain cardiovascular ailments. Little wonder that some conscious individuals are cautious in choosing their meals owing to this trepidation. It therefore becomes imperative to undertake a study on related works with a view to giving suitable medical information to arm individuals with reliable data towards the trend. Keywords – Food, diets, fats, cardiovascular diseases, heart attack.